2(x-3)+5x=5+7(x+3)

Simple and best practice solution for 2(x-3)+5x=5+7(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-3)+5x=5+7(x+3) equation:


2(x-3)+5x=5+7(x+3)

We simplify the equation to the form, which is simple to understand
2(x-3)+5x=5+7(x+3)

Reorder the terms in parentheses
+(+2x-6)+5x=5+7*(x+3)

Remove unnecessary parentheses
+2x-6+5x=+5+7+*(+x+3+)

Reorder the terms in parentheses
+2x-6+5x=5+(+7x+21)

Remove unnecessary parentheses
+2x-6+5x=+5+7x+21

We move all terms containing x to the left and all other terms to the right.
+2x+5x-7x=+5+21+6

We simplify left and right side of the equation.
0x=+32

0=32

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| 1=-8+2x | | -9=2v-3 | | 6x-(2x-3)=4x+5 | | x^4+4x^3+12x^2+12x-9=0 | | X/3+6=11 | | -5s=-1.25 | | 13x+19y=-17 | | 6x+75=9x+93 | | -2+8(x-5)=13x+6-5x | | -3(y-0.5)=0.5 | | -8.978=1.34t | | 3x(2-4)=24 | | -0.67(x+1)=6 | | 4(a-5)+6=2(a-6) | | 8x-3=7(x+5)+4 | | -5s=1.25 | | 3/4x-1=7/5 | | 9x-2=6x+43 | | -3=5(z+7) | | 3X+8Y=30 | | 24=-8y | | 4x^2-19x+24=-2x+9 | | 4x^2-16x+24=-2x+9 | | 12(r-2)=0 | | (8r-64)/4 | | 8r-64/4 | | (X^3+9x^2+7x-24)/(x-2) | | (7/4)x=56 | | 9/1-27/7 | | .5=.5555 | | 12x+3+4x=48 | | 4ax+5ab= |

Equations solver categories